2016
DOI: 10.1111/1750-3841.13337
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Lactobacillus rhamnosus GG by Transglutaminase Cross‐Linked Soy Protein Isolate to Improve Survival in Simulated Gastrointestinal Conditions and Yoghurt

Abstract: Microencapsulation is an effective way to improve the survival of probiotics in simulated gastrointestinal (GI) conditions and yoghurt. In this study, microencapsulation of Lactobacillus rhamnosus GG (LGG) was prepared by first cross-linking of soy protein isolate (SPI) using transglutaminase (TGase), followed by embedding the bacteria in cross-linked SPI, and then freeze-drying. The survival of microencapsulated LGG was evaluated in simulated GI conditions and yoghurt. The results showed that a high microenca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…In addition, gelation of soy proteins can also be induced by enzymes. Transglutaminase induced soy protein gelation for plant-based yogurt with encapsulated probiotics [ 24 ]. Previous studies suggested that soy protein could have a similar isoelectric point to casein [ 25 , 26 ] and its high gelation potential [ 22 ] could be influenced by its endogenous peptidases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gelation of soy proteins can also be induced by enzymes. Transglutaminase induced soy protein gelation for plant-based yogurt with encapsulated probiotics [ 24 ]. Previous studies suggested that soy protein could have a similar isoelectric point to casein [ 25 , 26 ] and its high gelation potential [ 22 ] could be influenced by its endogenous peptidases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various enzymes, acidic pH and presence of bile will threaten the viability of probiotic (Cook et al, 2012). When free LGG cells were sequentially incubated in SOJ for one hour, the survivability of LGG reduced drastically (p < 0.05) to 0% and this demonstrated that free cells had high sensitivity of LGG towards simulated gastrointestinal condition (Burgain et al, 2013;Li et al, 2016). On contrast, all encapsulated LGG had higher survival rate than free LGG cells during the first and second hour of SGJ incubation, which indicated that microencapsulation improved the survivability of LGG in gastric condition.…”
Section: Morphology Size and Microencapsulation Efficiency Of Beadmentioning
confidence: 97%
“…These finding are in common with Delikanli and Ozcan (2016) indicated that MPC supplementation improves mouthfeel and taste of yogurt samples in comparison with other milk base fortificants, which could be related to an increase in density of the protein matrix and improved textural properties. Higher acceptability of samples containing microencapsulated samples could be related to dual hydration effect of gellan–caseinate and production of EPS of used probiotics (Li et al , 2016). As hydrocolloid gelation methods lead to sandiness problem in yogurt, so the microencapsulation of probiotics by milk protein gelation methods can be a suitable alternative to polysaccharide gelation technologies like alginate (El-Salam and El-Shibiny, 2015).…”
Section: Resultsmentioning
confidence: 99%